2016
DOI: 10.1016/j.jvs.2015.09.049
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes for forearm and upper arm arteriovenous fistula creation with the transposition technique

Abstract: With low primary failure rates, reduced need for secondary interventions before maturation, and 1-year primary assisted patency rates in excess of 93%, our study showed that the transposition technique, in our experience, is superior to previously published literature in hemodialysis access creation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 15 publications
1
13
2
Order By: Relevance
“…Many of the existing studies concerning AVG and its role in long-term haemodialysis are retrospective [22,23,56] with only one prospective multicenter trial comparing AVG to TBB-AVF [35]. In summary, these studies found that while AVG provided comparable access patency, they carried higher rates of all-cause mortality, morbidity, re-intervention, readmission and overall institutional costs.…”
Section: Discussionmentioning
confidence: 99%
“…Many of the existing studies concerning AVG and its role in long-term haemodialysis are retrospective [22,23,56] with only one prospective multicenter trial comparing AVG to TBB-AVF [35]. In summary, these studies found that while AVG provided comparable access patency, they carried higher rates of all-cause mortality, morbidity, re-intervention, readmission and overall institutional costs.…”
Section: Discussionmentioning
confidence: 99%
“…29 Prior to AVF creation, CVC use occurred in 35.7-77.4% of patients. 13,21,26,30,31 A study investigating the natural history of AVFs noted that 66% of vascular access procedures were to create an AVF, with 33% of these being RCAVFs. 26 Four studies reported that 48-75% of AVFs were being used for HD at the time of follow-up, while 37-51% of them were abandoned.…”
Section: Patient Outcomesmentioning
confidence: 99%
“…Four studies reported an average AVF maturation time of 148-285 days with a cumulative functional 1-year patency of 60-70%. 1,21,26,32 Primary failure was recorded in 3 studies and occurred in 20-26% of cases. 25,26,31 In one study, AVFs failed to mature 20% of the time.…”
Section: Avf Outcomesmentioning
confidence: 99%
See 2 more Smart Citations